Sea surface temperature, rather than land mass or geographic distance, may drive genetic differentiation in a species complex of highly dispersive seabirds. Issue 21 (4th October 2021) - Torres, Lucas; Pante, Eric; González‐Solís, Jacob; Viricel, Amélia; Ribout, Cécile; Zino, Francis; MacKin, Will; Precheur, Carine; Tourmetz, Julie; Calabrese, Licia; Militão, Teresa; Zango, Laura; et al.
Abstract: Seabirds, particularly Procellariiformes, are highly mobile organisms with a great capacity for long dispersal, though simultaneously showing high philopatry, two conflicting life‐history traits that may lead to contrasted patterns of genetic population structure. Landmasses were suggested to explain differentiation patterns observed in seabirds, but philopatry, isolation by distance, segregation between breeding and nonbreeding zones, and oceanographic conditions (sea surface temperatures) may also contribute to differentiation patterns. To our knowledge, no study has simultaneously contrasted the multiple factors contributing to the diversification of seabird species, especially in the gray zone of speciation. We conducted a multilocus phylogeographic study on a widespread seabird species complex, the little shearwater complex, showing highly homogeneous morphology, which led to considerable taxonomic debate. We sequenced three mitochondrial and six nuclear markers on all extant populations from the Atlantic ( lherminieri ) and Indian Oceans ( bailloni ), that is, five nominal lineages from 13 populations, along with one population from the eastern Pacific Ocean (representing the dichrous lineage). We found sharp differentiation among populations separated by the African continent with both mitochondrial and nuclear markers, while only mitochondrial markers allowed characterizing the five nominal lineages. No differentiation could be detected within these five lineages, questioning the strong level of philopatry showed by these shearwaters. Finally, we propose that Atlantic populations likely originated from the Indian Ocean. Within the Atlantic, a stepping‐stone process accounts for the current distribution. Based on our divergence time estimates, we suggest that the observed pattern of differentiation mostly resulted from historical and current variation in sea surface temperatures. Abstract : We conducted a multilocus phylogeographic study on a widespread shearwater and sequenced three mitochondrial and six nuclear markers on all extant populations. We found sharp differentiation among populations separated by the African continent with both markers, while only mitochondrial markers allowed characterizing the five nominal lineages. We propose that Atlantic populations originated from the Indian Ocean. Within the Atlantic, a stepping‐stone process accounts for the current distribution.